Accelerated isotropic sub‐millimeter whole‐heart coronary MRI: Compressed sensing versus parallel imaging. Issue 2 (25th February 2013) - Akçakaya, Mehmet; Basha, Tamer A.; Chan, Raymond H.; Manning, Warren J.; Nezafat, Reza
<x xml:space="preserve">Abstract</x> Purpose To enable accelerated isotropic sub‐millimeter whole‐heart coronary MRI within a 6‐min acquisition and to compare this with a current state‐of‐the‐art accelerated imaging technique at acceleration rates beyond what is used clinically. Methods Coronary MRI still faces major challenges, including lengthy acquisition time, low signal‐to‐noise‐ratio (SNR), and suboptimal spatial resolution. Higher spatial resolution in the sub‐millimeter range is desirable, but this results in increased acquisition time and lower SNR, hindering its clinical implementation. In this study, we sought to use an advanced B1‐weighted compressed sensing technique for highly accelerated sub‐millimeter whole‐heart coronary MRI, and to compare the results to parallel imaging, the current‐state‐of‐the‐art, where both techniques were used at acceleration rates beyond what is used clinically. Two whole‐heart coronary MRI datasets were acquired in seven healthy adult subjects (30.3 ± 12.1 years; 3 men), using prospective 6‐fold acceleration, with random undersampling for the proposed compressed sensing technique and with uniform undersampling for sensitivity encoding reconstruction. Reconstructed images were qualitatively compared in terms of image scores and perceived SNR on a four‐point scale (1 = poor, 4 = excellent) by an experienced blinded reader. Results The proposed technique resulted in images with clear visualization of all coronary branches. Overall image quality and perceived SNR of the compressed sensing images were significantly higher than those of parallel imaging (P = 0.03 for both), which suffered from noise amplification artifacts due to the reduced SNR. Conclusion The proposed compressed sensing‐based reconstruction and acquisition technique for sub‐millimeter whole‐heart coronary MRI provides 6‐fold acceleration, where it outperforms parallel imaging with uniform undersampling. Magn Reson Med 71:815–822, 2014. © 2013 Wiley Periodicals, Inc.